PERILAKU GENERASI Z TERHADAP POTENSI ARROGANCE DAN COLLUSION DALAM FRAUD - Syifa' Sirojudin Anjay (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
Financial fraud is a serious issue that can be influenced by individual behavior. Generation Z, shaped by technological advancement and social media, has distinctive behavioral patterns that may contribute to the emergence of arrogance and collusion, in line with the Fraud Hexagon theory. This study aims to analyze the relationship between Generation Z’s behavior in terms of ethics, mindset, and motivation and the potential emergence of arrogance and collusion. The method used is a literature review with a qualitative descriptive approach, utilizing secondary data from global survey reports (McKinsey, Deloitte) and scientific literature. The results show that Generation Z’s behavior is linked to the risks of arrogance and collusion, either reinforcing or weakening the potential for fraud. These findings provide insight for developing fraud prevention strategies based on generational behavior.